The Social History of the Qadiriyah wa Naqsyabandiyah Order and Its Implications in the Social Environment - Arifinta, Hasna Nisa; Umami, Riza Maratul; Afifandasari, Thriska (Journal of Islamic and Social Studies, 2025)
The development of tarekat in Indonesia is very rapid, one of which is the development of the Qadiriyah wa Naqsyabandiyah tarekat. This article aims to simply describe the history of the establishment of Tarekat Qadiriyah wa Naqsyabandiyah and the implications of its teachings in the social environment. The method used in this research is literature study by collecting information related to Tarekat Qadiriyah wa Naqsyabandiyah in books and other literature. The results showed that Tarekat Qadiriyah wa Naqsyabandiyah was founded by a Sheikh from Indonesia by combining and modifying the teachings of Tarekat Qadiriyah and Tarekat Naqsyabandiyah. The implications in the social environment can be seen from the main teachings that are applied in everyday life.